Smart Museum for Nepal Cultural Heritage Information Exchange System - Sharma, Gajendra; Chandra Gurung, Ravi (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
Smart Museum is a study focus on Nepal Cultural Heritage information exchange system. The main objective is to provide innovative and interactive approaches which could enhance visitors experience in the museum. Its concept is based upon smart museum that is integrating digital museum contents with information exchange by using Near Field Communication (NFC) smart tags and Quick Response (QR) code. Visitors can use their smart phone to get detail information without help of anyone. The study focuses on detail research about short distance communication network that includes NFC and QR code as of RFID technologies. Back-end system is used for providing detail information of artefacts and preservation of museum in the digital format. Mobile Software Development Life Cycle (MSDLC) was chosen for the development of the application. It was used for its development criteria covered all the aspects. The study requirements were straight forward where many factories were not much changed. MSDLC was found shorter life cycle since mobile applications needs to develop in rapid due to the market competition. Most of the museums were found under-developed as per the requirements. The direct museums visited done were found also interested on the upgrading the museum services however lack of the proper management leaded to not able to do so.